2018
DOI: 10.1016/j.celrep.2018.09.013
|View full text |Cite
|
Sign up to set email alerts
|

XBP1-KLF9 Axis Acts as a Molecular Rheostat to Control the Transition from Adaptive to Cytotoxic Unfolded Protein Response

Abstract: SUMMARY Transcription factor XBP1s, activated by endoplasmic reticulum (ER) stress in a dose-dependent manner, plays a central role in adaptive unfolded protein response (UPR) via direct activation of multiple genes controlling protein refolding. Here, we report that elevation of ER stress above a critical threshold causes accumulation of XBP1s protein sufficient for binding to the promoter and activation of a gene encoding a transcription factor KLF9. In comparison to other XBP1s targets, KLF9 promoter contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 33 publications
1
40
2
Order By: Relevance
“…Firstly, it was shown that overexpression of XBP1s induced apoptosis in human umbilical endothelial cells [99]. Secondly, a recent report showed that while XBP1 mediated adaptive signals at noncytotoxic, low levels of ER stress, it could mediate proapoptotic effects via upregulating the expression of the transcription factor KLF9 at cytotoxic, high levels of ER stress in WI38 human fibroblasts [100]. Although the effect of XBP1 depletion on ER stress-induced cell death was not examined in the latter report, these studies and ours together suggest that the IRE1-XBP1 axis provides pro-death signals under high-level ER stress conditions and that this may contribute to ER stress-induced cell death in several different cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, it was shown that overexpression of XBP1s induced apoptosis in human umbilical endothelial cells [99]. Secondly, a recent report showed that while XBP1 mediated adaptive signals at noncytotoxic, low levels of ER stress, it could mediate proapoptotic effects via upregulating the expression of the transcription factor KLF9 at cytotoxic, high levels of ER stress in WI38 human fibroblasts [100]. Although the effect of XBP1 depletion on ER stress-induced cell death was not examined in the latter report, these studies and ours together suggest that the IRE1-XBP1 axis provides pro-death signals under high-level ER stress conditions and that this may contribute to ER stress-induced cell death in several different cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Activated IRE1α splices XBP1 mRNA, which encodes transcription factor to increase the protein-folding capacity and degrade misfolded proteins. While IRE1α engages STAT3 pathway to promote liver regeneration upon liver injury 26 , XBP1 switches prosurvival to proapoptotic signal cascades through multiple gene regulation 27,28 . It has been reported that ATF6 exerts a pro-inflammatory effect on ischemiareperfusion liver injury 29 .…”
Section: Discussionmentioning
confidence: 99%
“…KLF9 can be induced by several physiological or pathological stresses. Current experimental evidence indicates that KLF9 plays a key hormone-dependent role in liver gluconeogenesis (9). Notably, a recent study indicated that KLF9 is induced by NF-E2-like basic leucine zipper transcriptional activator (Nrf2), thereby promoting cell oxidative stress (7).…”
Section: Introductionmentioning
confidence: 99%